Controlling the exciton emission of gold coated GaAs–AlGaAs core–shell nanowires with an organic spacer layer. (4th November 2016) - Kaveh, M; Gao, Q; Jagadish, C; Ge, J; Duscher, G; Wagner, H P
Abstract: Excitons are the most prominent optical excitations and controlling their emission is an important step towards new optical devices. We have investigated the exciton emission from uncoated and gold/aluminum quinoline (Alq3 ) coated GaAs–AlGaAs–GaAs core–shell nanowires (NWs) using temperature-, intensity- and polarization dependent photoluminescence (PL). Plasmonic GaAs–AlGaAs–GaAs NWs with a ∼10 nm thick Au coating but without an Alq3 spacer layer reveal a significant reduction of the PL intensity of the exciton emission compared with the uncoated NW sample. Plasmonic NW samples with the same nominal Au coverage and an additional Alq3 interlayer of 3 or 6 nm thickness show a clearly stronger PL intensity which increases with rising Alq3 spacer thickness. Time-resolved (TR) PL measurements reveal an increase of the exciton decay rate by a factor of up to two with decreasing Alq3 spacer thickness suggesting the presence of Förster energy transfer from NW excitons to plasmon oscillations in the gold film. The weak change of the decay time, however, indicates that Förster energy-transfer is only partially responsible for the PL quenching in the gold coated NWs. The main reason for the reduction of the PL emission is attributed to a gold induced band-bending in the GaAs NW core which causes exciton dissociation. With increasing Alq3 spacer thickness the band-bending decreases leading to a reduction of the exciton dissociation and PL quenching. Our interpretation is supported by electron energy loss spectroscopy measurements which show a signal reduction and blue shift of defect (possibly EL2) transitions when gold particles are deposited on NWs compared with bare or Alq3 coated NWs.